2012
DOI: 10.1152/jn.00756.2010
|View full text |Cite
|
Sign up to set email alerts
|

Two hands, one perception: how bimanual haptic information is combined by the brain

Abstract: Humans routinely use both of their hands to gather information about shape and texture of objects. Yet, the mechanisms of how the brain combines haptic information from the two hands to achieve a unified percept are unclear. This study systematically measured the haptic precision of humans exploring a virtual curved object contour with one or both hands to understand if the brain integrates haptic information from the two hemispheres. Bayesian perception theory predicts that redundant information from both han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The current results are similar to the results of Squeri et al (2012) in many respects. That study investigated the perception of surface curvature and found that while the nondominant left hand typically was superior at curvature perception, the right hand was a better predictor of bimanual curvature.…”
Section: Discussionsupporting
confidence: 90%
“…The current results are similar to the results of Squeri et al (2012) in many respects. That study investigated the perception of surface curvature and found that while the nondominant left hand typically was superior at curvature perception, the right hand was a better predictor of bimanual curvature.…”
Section: Discussionsupporting
confidence: 90%
“…Although previous studies have shown that haptic perception in the absence of cutaneous input is diminished when discriminating some object properties, such as surface compliance [3], recent evidence suggests a greater role for kinesthetic input in forming neural representations of geometric object features, such as its shape or size, than previously believed [4], [5], [6], [7], [8], [9]. For example, Voisin et al [10] asked participants to discriminate concave angles of physical surfaces by tracing surface outlines with the index finger using a dynamic mode of exploration.…”
Section: Introductionmentioning
confidence: 86%
“…Henriques and Soechting [14] found reliable curvature discrimination in the active mode of exploration, in which participants were allowed to freely explore the surface using the robotic arm. Further, Squeri et al found evidence for curvature discrimination in both active [8] and passive [9] exploration modes. These results suggest that although both cutaneous and kinesthetic inputs contribute to haptic perception of curvature, each input itself may make a reliable contribution.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, individuals have been asked to tactically identify numbers (Heller, Rogers & Perry, 1990) and letters (O'Boyle, Van Wyhe-Lawler & Miller, 1987, including Braille: e.g. Hermelin & O'Connor, 1971Wilkinson & Carr, 1987) or haptically assess and discriminate between object properties including: thickness (Cormier & Tremblay, 2013), roughness (Tomlinson, Davis, Morgan & Bracewell, 2011), curvature (Squeri et al, 2012), shape (Fagot, Hopkins & Vauclair, 1993a;Fagot, Lacreuse & Vauclair, 1993b), or hardness (Morange-Majoux, 2011) for various objects. For instance, O'Boyle et al (1987) traced capital letters onto the palms of individuals and found that accuracy was higher when the letter was traced onto the left hand.…”
Section: Introductionmentioning
confidence: 99%